External Wealth, the Trade Balance, and the Real Exchange Rate - Lane, Philip (IMF Working Papers; Working Paper ;, 2002)
This paper examines the link between the net foreign asset position, the trade balance and the real exchange rate. In particular, it decomposes the impact of a country's net foreign asset position ("external wealth") on its long-run real exchange rate into two mechanisms: the relation between external wealth and the trade balance; and, holding other determinants fixed, a relation between the trade balance and the real exchange rate. It also provides additional evidence that the relative price of nontradables is an important channel linking the trade balance and the real exchange rate.